Is liquidity the missing link? - Limkriangkrai, M.; Durand, Robert; Watson, I. (Wiley-Blackwell Publishing Asia, 2008)
Durandet al.(2006a) argue that the Australian market is both internationallyintegrated and domestically segmented. They find that the US-based three-factormodel captures returns of the largest stocks in Australia (evidence of internationalintegration), but that it is unable to account for the returns of the smallest stocks(evidence of domestic segmentation). This study resolves the puzzle left by Durandet al. (2006a). Incorporating a liquidity factor provides the missing link in theiranalysis: it results in a model that permits both the international integration of thelargest stocks and the model can account for the returns of the smallest stocks.Our analysis highlights the important role of liquidity in Australian asset pricing.